2016
DOI: 10.1017/jgc.2016.20
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Online and Face-to-Face Student Counselling: What Therapeutic Goals Are Identified and What Are the Implications for Educational Providers?

Abstract: Online counselling is increasingly being used as an alternative to face-to-face student counselling. Using an exploratory mixed methods design, this project investigates the practice by examining the types of therapeutic goals that 11 to 25 year olds identify online in routine practice. These goals are then compared to goals identified in equivalent school and community-based counselling services. 1,137 online goals (expressed by 504 young people) and 221 face-to-face goals (expressed by 220 young people) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…The issues young people bring to online counselling were wide ranging and included abuse/ violence, family/peer relationships, self-harm, depression, sexual abuse/rape, anxiety/stress, alcohol/drug misuse, anger, self-esteem, sex/sexuality issues and eating disorders. Four studies compared their online sample's presenting issues with other means of counselling (Callahan and Inckle, 2012;Hanley et al, 2016;King et al, 2006b;Sefi and Hanley, 2012). In doing so, these studies found that the online sample appeared to present with different reasons to the comparison group.…”
Section: Online Client Characteristicsmentioning
confidence: 99%
“…The issues young people bring to online counselling were wide ranging and included abuse/ violence, family/peer relationships, self-harm, depression, sexual abuse/rape, anxiety/stress, alcohol/drug misuse, anger, self-esteem, sex/sexuality issues and eating disorders. Four studies compared their online sample's presenting issues with other means of counselling (Callahan and Inckle, 2012;Hanley et al, 2016;King et al, 2006b;Sefi and Hanley, 2012). In doing so, these studies found that the online sample appeared to present with different reasons to the comparison group.…”
Section: Online Client Characteristicsmentioning
confidence: 99%
“…Studies indicate that the motivations underpinning young peopleā€™s selection of TBOC modalities center on perceptions of its heightened safety due to environmental privacy, anonymity, autonomy, control, and emotional distance from the counsellor as well as its increased accessibility due to its convenience, ease of access, and affordability [35,38,49,52-55]. Other motivations include a preference for text communication and polarized minimal or heightened expectations about the outcome of counseling [37,56,57]. Studies indicate that most common presenting problems for young people accessing TBOC are related to mental health, relationships, and information-related requests (eg, medico-legal questions, service referrals, and resource requests) [31,38,39,48,58], with some evidence suggesting that service users experience a higher level of distress or perceived burden of the problem than those presenting on telephone-based modalities [39,50,51].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, individuals may choose to access a combination of resources, with informative static webpages about particular issues, peer discussion forums, and professional support and guidance. The desire to obtain different types of support has previously been observed in the goals articulated by clients in web-based therapy [ 52 ] and the way that individuals use online forums [ 53 ]. Therefore, psychological services that offer anonymous therapy and support on the web need to be prepared to offer a variety of resources to accommodate the informational and emotional needs for which individuals access services.…”
Section: Discussionmentioning
confidence: 99%